CONTRA CONTINUOUS FUNCTIONS, CONNECTEDNESS AND COMPACTNESS - parvathy, chennimalai ramanathan (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
In this paper, we apply the notion of Irwg- open sets to present and the study a new class of functions called Irwg -contra -continuous functions in ideal topological spaces. This paper deals with Irwg – connected spaces and their properties. Also Irwg – compact spaces is introduced and their properties are studied.